The QMSA: how students' self-assessment can be a resource to learn and redirect teaching practices - Arianna Giuliani (Firenze University Press, 2020)
The scientific community has been wondering for some time about the strategies that can be effective in favoring a self-assessment of students that is configured as an assessment for learning and on the importance of enhancing the evidence that emerged from internal and external assessments to qualify educational and teaching practices (Aquario & Grion, 2017; Domenici & Lucisano, 2011; Weeden, Winter, & Broadfoot, 2009). The paper deepens the Questionnaire on Motivation and Learning Strategies (QMSA), adapted to the Italian context by Moretti, Giuliani and Morini in 2018 and of which the Confirmatory Factor Analysis is presented. The QMSA allows to detect information on subjects in learning useful to identify a multidimensional profile of the student and to work on didactic interventions aimed at the specific needs that emerged. The QMSA is an easy-to-use tool in the university environment and the information it detects can be a resource for qualifying students' self-assessment processes and for redirect teaching practices.   Il QMSA: come l'autovalutazione degli studenti può essere una risorsa per apprendere e riorientare le pratiche didattiche La comunità scientifica si interroga da tempo sulle strategie che possono essere efficaci per favorire una autovalutazione degli studenti che si configuri come valutazione per l'apprendimento e sull'importanza di valorizzare le evidenze emerse da valutazioni interne ed esterne per qualificare le pratiche educative e didattiche (Aquario & Grion, 2017; Domenici & Lucisano, 2011; Weeden, Winter, & Broadfoot, 2009). Il contributo approfondisce il Questionario sulla Motivazione e sulle Strategie di Apprendimento (QMSA), adattato al contesto italiano da Moretti, Giuliani e Morini nel 2018 e di cui si presenta l'Analisi Fattoriale Confermativa. Il QMSA consente di rilevare informazioni sui soggetti in apprendimento utili per individuare un profilo multidimensionale dello studente e lavorare su interventi didattici mirati alle esigenze specifiche emerse. Il QMSA è uno strumento di agevole utilizzo in ambito universitario e le informazioni che rileva possono essere una risorsa per qualificare i processi di autovalutazione degli studenti e per riorientare le pratiche didattiche.